Storytelling as an Act of Subversion: Call for Action in Hulu’s TV Series The Handmaid’s Tale - Kaličanin, Milena (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
The article focuses on the comparative analysis of Margaret Atwood’s 1985 novel and Bruce Miller’s (2017) TV adaptation of The Handmaid’s Tale. Special attention in the paper is given to the construction of the main character’s identity in the respective media, most particularly the fact that in the Hulu series (2017-2022) the main character is depicted as a modern feminist activist constantly offering resistance to repressive ideology, unlike in the novel in which her new identity completely erases memories of prior existence and is compliant with inhuman treatment in Gilead. Just like Atwood, Miller applies the strategy of the interior monologue and intensifies its impact by using voice-over narration and italic subtitles that turn the audience into a secret confidante and willing ally in the main character’s struggle against repressive heteronormative and misogynist rules. This thought-provoking platform of expression is purposefully used by Miller in order to emphasize the importance of storytelling as a subversive act of resistance. With the help of Atwood herself, who has been collaborating with the series cast, producers, and director in screenwriting, this TV adaptation draws attention to contemporary issues of political conflicts, sexual slavery, war, toxic pollution, poverty, LGBTQ, women’s rights, as well as the need to address these issues and ultimately influence a long-craved social reform. The theoretical framework of the research relies on the concepts of transmedial narratology as elaborated by Thon (2015, 2016), Ryan (2014), Rajewski (2005), Gobyn (2019) and others.
Keywords: subversion, storytelling, transmedial narratology, remediation, interior monologue, ideology, identity, feminism.